Recreation: a social act for the construction of the human (Impetus, 2021)
Today it is clear to think that one of the most important bets that the human recreation laboratory, as a research line and project, is to understand and demonstrate the real dimensions of recreation, an effort that is directed towards the need to specify a body real theoretical that together with the experience gathered from the practical exercises in this field, become the entrance to a world where recreation is seen as a complex act that majestically stimulates the concept of the human.